Integrasi Pendidikan Rumah dan Sekolah Membangun Karakter Anak di Era Society 5.0 - Firmansyah, Rully Agung; Hanifah, Fa’izah; Sunarsih; Aziz, Fatoni; Khoiriyah (Educational Research Center, 2026)
The Society 5.0 era presents new challenges in the formation of children's characters, including the use of digital technology, social media, and changes in social interaction patterns as well as access to negative content that has the potential to weaken religious values, manners, and morals. The research aims to analyze and formulate an effective home-school education integration model to build children's character in the Society 5.0 era based on the principles of Islamic education. The research uses a qualitative approach of the type of literature study, with data sources in the form of books on family and character education, home-school education integration, education in the digital era, journal articles of the last five years, as well as classical and contemporary Islamic literature on tarbiyah, adab, and moral formation. Data analysis is carried out through content analysis techniques through the stages of data reduction, concept classification, interpretation, and conclusion drawn. The results of the study show that the family plays a role as the first madrasah in the cultivation of monotheism, worship, manners, and morals, while the school plays a role in strengthening these values formally and systematically through learning that is adaptive to technology. Children's character challenges in the Society 5.0 era such as cyberbullying, individualism, decreased empathy, and negative content consumption demand strengthening Islamic digital literacy. The integration model includes monotheism, worship, manners, social morals, and digital literacy through strategic, communicative, and sustainable collaboration between parents and schools. The integration of home and school education based on Islamic principles is able to strengthen the character of children who have faith, noble character, and are wise in utilizing technology in the Society 5.0 era.